Long-Term Follow-Up of Pericardium for the Ventricular Component in Atrioventricular Septal Defect Repair. Issue 6 (November 2020) - IJsselhof, Rinske J.; Duchateau, Saniyé D. R.; Schouten, Rianne M.; Slieker, Martijn G.; Hazekamp, Mark G.; Schoof, Paul H.
Background: Despite the improved outcome in complete atrioventricular septal defect (AVSD) repair, reoperations for left atrioventricular valve (LAVV) dysfunction are common. The aim of this study was to evaluate the effect of fresh untreated autologous pericardium for ventricular septal defect (VSD) closure on atrioventricular valve function and compare the results with the use of treated bovine pericardial patch material. Methods: Clinical and echocardiographic data were collected of patients with complete AVSD with their VSD closed with either untreated autologous pericardial or treated bovine pericardial patch material between January 1, 1996, and December 31, 2003. Evaluation closed in September 2019. Results: A total of 77 patients were analyzed (untreated autologous pericardial VSD patch: 59 [77%], treated bovine pericardial VSD patch: 18 [23%]). Median age at surgery was 3.6 (interquartile range [IQR]: 2.7-4.5) months, and median weight was 4.5 (IQR: 3.9-5.1) kg. Trisomy 21 was present in 70 (91%) patients. Median follow-up time was 17.5 (IQR: 12.6-19.8) years. Death <30 days occurred in two (3%) patients. Reinterventions occurred in eight patients (early [within 30 days] in two, early and late in one, and late in five), all in the autologous pericardium group. Log-rank tests showed no significant difference in mortality ( P = .892), LAVV reinterventions ( P = .228), or LAVV regurgitation ( P = .770). Conclusions: In AVSD, the VSD can safely be closed with either untreated autologous pericardium or xeno-pericardium. We found no difference in LAVV regurgitation or the need for reoperation between the two patches.